Production of Oxidants by Ion Bombardment of Icy Moons in the Outer Solar System. (8th February 2012) - Boduch, Philippe; da Silveira, Enio Frota; Domaracka, Alicja; Gomis, Oscar; Lv, Xue Yang; Palumbo, Maria Elisabetta; Pilling, Sergio; Rothard, Hermann; Seperuelo Duarte, Eduardo; Strazzulla, Giovanni
Abstract : Our groups in Brazil, France and Italy have been active, among others in the world, in performing experiments on physical-chemical effects induced by fast ions colliding with solids (frozen gases, carbonaceous and organic materials, silicates, etc.) of astrophysical interest. The used ions span a very large range of energies, from a few keV to hundreds MeV. Here we present a summary of the results obtained so far on the formation of oxidants (hydrogen peroxide and ozone) after ion irradiation of frozen water, carbon dioxide and their mixtures. Irradiation of pure water ice produces hydrogen peroxide whatever is the used ion and at different temperatures. Irradiation of carbon dioxide and water frozen mixtures result in the production of molecules among which hydrogen peroxide and ozone. The experimental results are discussed in the light of the relevance they have to support the presence of an energy source for biosphere on Europa and other icy moons in the outer Solar System.